Ethics and animals : an introduction - Gruen, Lori (Cambridge applied ethics, 2011)
"In this fresh and comprehensive introduction to animal ethics, Lori Gruen weaves together poignant and provocative case studies with discussions of ethical theory, urging readers to engage critically and empathetically reflect on our treatment of other animals. In clear and accessible language, Gruen provides a survey of the issues central to human-animal relations and a reasoned new perspective on current key debates in the field. She analyses and explains a range of theoretical positions and poses challenging questions that directly encourage readers to hone their ethical reasoning skills and to develop a defensible position about their own practices. Her book will be an invaluable resource for students in a wide range of disciplines including ethics, environmental studies, veterinary science, women's studies, and the emerging field of animal studies and is an engaging account of the subject for general readers with no prior background in philosophy"--